Sycamore row - Grisham, John (Doubleday, 2013)
When wealthy Seth Hubbard hangs himself from a sycamore tree and leaves his fortune to his black maid, Jake Brigance once again finds himself embroiled in a fiercely controversial trial -- a trial that will expose old racial tensions and force Ford County to confront its tortured history.